2023
DOI: 10.1063/5.0135583
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of Wenzel-state nanodroplets: Evaporation on heated substrates with different rough structures

Abstract: To study the evaporation characteristics of nanodroplets on substrates with different rough structures, molecular dynamics simulations have been performed. Based on the Wenzel wetting model, three systems with different rough structures were constructed, in which the ratios of contact area (RCA) between substrates and nanodroplets were 33.3%, 50% and 66.6%, respectively. The results indicate that the evaporation pattern of the nanodroplet in the system with RCA = 33.3% is the mixed mode, the evaporation patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In other words, when the size of the nanodroplet is equivalent to the size of the rough structure, the pinning effect becomes prominent. Bi et al 48 studied the effect of the proportion of the rectangular rough structure in the substrate on the nanodroplet evaporation by using MD simulations. The results of their study suggest that the change of the proportion of rough structure would change the wettability of the substrate, thus affecting the dynamics, as well as the heat and mass transfer during the evaporation of the nanodroplet.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, when the size of the nanodroplet is equivalent to the size of the rough structure, the pinning effect becomes prominent. Bi et al 48 studied the effect of the proportion of the rectangular rough structure in the substrate on the nanodroplet evaporation by using MD simulations. The results of their study suggest that the change of the proportion of rough structure would change the wettability of the substrate, thus affecting the dynamics, as well as the heat and mass transfer during the evaporation of the nanodroplet.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such investigations generally face challenges at the microscales as evaporation is in principle a nonequilibrium process, but undoubtedly molecular dynamics (MD) simulations can contribute to our understanding of this phenomenon. Hence, to achieve a more fundamental insight into the underlying mechanisms of evaporation on rough substrates, a series of MD simulation studies have been performed. For instance, Sun et al employed MD simulation to investigate the nanodroplet evaporation on heated rough substrates and proposed that the evaporation mode of a nanodroplet on a rough lyophilic substrate is the mixed mode, which is in contrast to the CCA or CCR modes observed in the case of macroscopic evaporation. In addition, they have suggested that the evaporation of nanodroplets on a rough lyophilic substrate is enhanced compared to a smooth lyophilic substrate, which has also been confirmed in the MD simulation work of Li et al However, a substrate with a wavy rough structure was used in the former, while a substrate with a rectangular rough structure was used in the latter.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the evaporation rate slows down when the droplet is nearly dried out in the nanoscale, which is different from the assumption of constant evaporation rate in the macroscale . In this regard, a series of simulations have been conducted including molecular dynamics (MD) and Monte Carlo (MC) simulations, yielding a range of intriguing findings. MD simulations , can record the position of each particle and obtain a comprehensive understanding of the evaporation dynamics. These models offer a suitable framework for describing the relevant phenomena at the microscale.…”
Section: Introductionmentioning
confidence: 99%